Electrochemical Sensor Based on Nanocomposite of Multi-Walled Carbon Nanotubes / TiO2 Nanoparticles in Chitosan Matrix for Simultaneous and Separate Determination of Dihydroxybenzene Isomers. Issue 5 (1st January 2018) - Fotouhi, Lida; Dorraji, Parisa Seyed; Keshmiri, Yasaman Sadat Seyed; Hamtak, Maryam
Abstract : The present research was conducted to develop a potent electrochemical sensor based on multi-walled carbon nanotubes and TiO2 nanoparticles in chitosan matrix (CS-MWCNTs+TiO2 NPs). In the CS-MWCNTs+TiO2 NPs nanocomposite film with excellent catalytic activities, good electrical conductivities and high surface areas of MWCNTs and TiO2 NPs, the simultaneous determination of hydroquinone (HQ), catechol (CC) and resorcinol (RS) with proper analytical performance was realized in the individual or triple-components solution in comparison with the bare glassy carbon electrode (GCE) and the single component modified GCE. The linear response of HQ, CC and RS were obtained in the ranges of 0.4–276.0 μmol dm −3, 0.4–159.0 μmol dm −3 and 3.0–657 μmol dm −3 and the detection limits (S/N = 3) were 0.06 μmol dm −3, 0.07 μmol dm −3, and 0.52 μmol dm −3, respectively. In the real water sample analysis by the developed sensor, satisfactory results were obtained.